Incidence of Creative Processes in Visual Arts Students (Docentes 2.0 Journal, 2021)
In the history of humanity focused on art, specifically on drawing and painting, there is the ability to represent reals, fictitious or abstract images on a surface, which can be very diverse and with different pigments. This research's objective was to analyze and incidence of the creative processes in the learning of the graphic-plastic expression of the portrait-self-portrait in the students of the first semester of Visual Arts, University of Pamplona. Therefore, was carried out a bibliographic review on the relevant aspects of the theory studied and the works in the international, national, and regional fields, which were very useful for the methodological design, approach, strategy, and analysis. From the results. The type of research was qualitative with the phenomenological method and began with a diagnostic stage where it was possible to establish a population characterized by five first-semester students plus three teachers who were of great importance for their contributions. With their subsequent analysis, information and discussion, the results led to the main conclusion: the creative processes did influence when drawing a face, knowing as a requirement a very acute perception since, for this reason, the graphic-plastic expression of the portrait- Self-portrait is very compelling for those who are learning to see and draw.
Keywords: Creative process; graphic-plastic; portrait; self-portrait